Tijolos prensados de solo-cimento confeccionados com resíduos de concreto - Souza, Márcia I. B. [UNESP]; Segantini, Antonio A. S. [UNESP]; Pereira, Joelma A. [UNESP] (FapUNIFESP (SciELO), 2008)
In this work results are presented of laboratory tests aiming to evaluate the possibility of using concrete wastes in manufactured soil-cement pressed bricks. Tests of characterization of used soil of the composite of this soil with concrete wastes and of the mixtures of soil cement made with this composite were evaluated. According to results of tests carried out with cylindrical specimens and with soil cement pressed bricks, it was verified that the addition of the concrete wastes improved soil cement mechanical properties, favoring the a reduction of the cement consumption, obtaining pressed bricks with a better quality.
Soil-cement pressed bricks made with concrete wastes
Keywords: Construction waste; Environment; Recycling